PENGARUH PENGGUNAAN MEDIA KARTU BERGAMBAR DALAM MODEL PEMBELAJARAN KOOPERATIF TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD NEGERI GUNUNG SARI KOTA MAKASSAR - Febrianti, Netti; Nawir, Muhammad; Arifin, Jamaluddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The main problem of this research is Is there any influence of the use of picture card media in the cooperative learning model on the learning outcomes of fifth-grade students of Gunung Sari 1 Makassar State Elementary School? The purpose of this study was to determine the effect of the use of picture card media in the cooperative learning model on the learning outcomes of fifth-grade students of Gunung Sari 1 Makassar State Elementary School. This type of research is experimental research in the form of a pre-experimental design used is one group pretest-posttest design general pre-test and post-test one group. The total sampling technique was chosen because the population is small and limited to one class, making it possible to cover all members without the need for random sampling. By using total sampling, the results of the study are expected to provide an accurate picture of the characteristics and conditions of all V.A class students without the risk of sampling errors of fifth-grade students of Gunung Sari 1 Makassar State Elementary School in the 2024/2025 academic year. The experimental unit in this study was 31 fifth-grade students. The results of this study indicate that teachers who use picture cards can improve student learning outcomes positively. The use of picture cards demonstrated improved learning outcomes compared to before the use of picture cards. The results of the inferential statistical analysis using the t-test formula showed a calculated t-value of 7.46 with a frequency of db = 31-1 = 30. At a significance level of 5%, the t-table value was 2.04. Therefore, the calculated t-table or null hypothesis (H₀) was rejected and the alternative hypothesis (Hₗ) was accepted. This proves that the use of picture cards has an effect on the learning outcomes of fifth-grade students at Gunung Sari 1 Elementary School, Makassar.